A New Stubby Species of Demodectic Mite (Acari: Demodicidae) From the Domestic Dog (Canidae). Issue 2 (4th January 2018) - Morita, Tatsushi; Ohmi, Aki; Kiwaki, Akihito; Ike, Kazunori; Nagata, Katsuyuki
Abstract: A new species of Demodex was detected in the earwax of a dog with otitis externa in Saitama Prefecture, Japan, in July 2010. The opisthosoma length of the mite was slightly shorter than 1/2 of its body length, which was different from the other species in domestic dogs, D. canis and D. injai, but was similar to the form of mites termed "short-bodied species", including D. cornei . However, the stubby external form was morphologically different from those of "short-bodied species", excluding a case without a species description reported from Greece. Among known species, the mite was similar to D. equi and D. acutipes .